STUDY OF THE IMPACT OF DYNAMIC AND CIRCULATION PROCESSES ON THE DISTRIBUTION OF anthropogenic and biogenic sea surface pollution ON THE BASE OF integrated use of satellite information - O. Yu. Lavrova; M. I. Mityagina; A. G. Kostianoy (Проблемы постсоветского пространства, 2017)
The article provides information about a research dedicated to the study of anthropogenic and biogenic pollution in the Russian seas on the basis of integrated use of satellite information, performed in Russian Space Research Institute. We discuss the goals and objectives of the project, state of the problem, methods and tools used for implementation of the project. Particular attention is paid to the expected results to be obtained upon completion of the project at the end of 2016.